SIAE - Stockholm International Art Expo 1981. - SIAE - Stockholm International Art Expo 1981 (Stockholm : SIAE (Stockholm International Art Expo), 1981)
Brom, Hal ; Reinhoud ; Pedersen, Carl-Henning ; Jacobsen, Robert ; Alechinsky, Pierre ; Bolin, Gustav ; Popova, Ljubov ; Pomié, Isac ; Eisner, Jeppe ; Fontana, Lucio ; Cane, Louis ; etc.
SIAE - Stockholm International Art Expo 1981, 1 - 5 april 1981
kunstcatalogus